What Do We Know about the Career Maturity of College Student-Athletes? A Brief Review and Practical Suggestions for Career Development Work with Student-Athletes - Kornspan, Alan S.; Etzel, Edward F. (My University, 2003)
The purpose of this article was to provide useful information concerning career maturity and college student-athletes. An overview of developmental tasks college students face and how they relate to career maturity will initially be presented. Next, the construct of career maturity will be discussed as it relates to two career development theories associated with the construct (i.e., Super and Crites). Practical suggestions on how to enhance student-athlete career maturity based on theory, research and the author's experiences will follow.
Keywords: career development